Effective co-delivery of doxorubicin and dasatinib using a PEG-Fmoc nanocarrier for combination cancer chemotherapy. (October 2015) - Zhang, Peng; Li, Jiang; Ghazwani, Mohammed; Zhao, Wenchen; Huang, Yixian; Zhang, Xiaolan; Venkataramanan, Raman; Li, Song
Abstract: A simple PEGylated peptidic nanocarrier, PEG5000 -lysyl-(α-Fmoc-ε-Cbz-lysine)2 (PLFCL), was developed for effective co-delivery of doxorubicin (DOX) and dasatinib (DAS) for combination chemotherapy. Significant synergy of DOX and DAS in inhibition of cancer cell proliferation was demonstrated in various types of cancer cells, including breast, prostate, and colon cancers. Co-encapsulation of the two agents was facilitated by incorporation of 9-Fluorenylmethoxycarbonyl (Fmoc) and carboxybenzyl (Cbz) groups into a nanocarrier for effective carrier-drug interactions. Spherical nanomicelles with a small size of ∼30 nm were self-assembled by PLFCL. Strong carrier/drug intermolecular π–π stacking was demonstrated in fluorescence quenching and UV absorption. Fluorescence study showed more effective accumulation of DOX in nuclei of cancer cells following treatment with DOX&DAS/PLFCL in comparison with cells treated with DOX/PLFCL. DOX&DAS/PLFCL micelles were also more effective than other treatments in inhibiting the proliferation and migration of cultured cancer cells. Finally, a superior anti-tumor activity was demonstrated with DOX&DAS/PLFCL. A tumor growth inhibition rate of 95% was achieved at a respective dose of 5 mg/kg for DOX and DAS in a murine breast cancer model. Our nanocarrier may represent a simple and effective system that could facilitate clinical translation of this promising multi-agent regimen in combination chemotherapy.